Farmer Groups, Input Access and Intragroup Dynamics: A Case Study of Targeted Subsidies in Nigeria - Liverpool-Tasie, Lenis Saweda O. (International Food Policy Research Institute, 2012)
Farmer groups are considered potentially effective mechanisms to increase farmer livelihood by reducing information asymmetries and transaction costs. In many countries, farmers are coordinated in groups for participation in poverty reduction programs. This is common practice in many input voucher programs in Sub-Saharan Africa. While the effect of farmer groups on certain outcomes such as price received and marketing has been studied, few studies, if any, have examined the effect of intragroup dynamics on farmer experience of input voucher programs. Consequently, this research uses a fertilizer voucher scheme in Nigeria to explore whether different methods of distributing fertilizer through farmer groups can affect an intervention’s ability to increase farmer access to agricultural inputs. To receive a fertilizer voucher in a pilot targeted subsidy program in Nigeria, all farmers were required to be members of an organized group. However, for fertilizer distribution among one set of participants, individual farmers were given their allotted share directly, whereas farmers in the other set received their fertilizer indirectly through a group representative.